Ship propulsion using wind, batteries and diesel-electric machinery - Dimensioning of a propulsion system using wind, batteries and diesel-electric machinery - Sandell, Jonas; Segerlind, Jonas (My University, 2016)
Wind energy is a resource that is not used to any great extent in the shipping industry since the advent of the internal combustion engine in the 1920s. Since then, wind power is utilized at sea in less extent until recent years. In this report, the authors will investigate how a ship that runs on wind power can reduce its bunker consumption, both directly and indirectly through wind energy. Directly is how the wind energy can relieve the engines on board and indirectly how a ship, with the help of wind assistance, can have smaller equipment on board to decrease the fuel consumption. The ship model for this report has a diesel-electric machinery and batteries that will help reduce consumption. To carry out this work the authors created a numerical model ship in MATLAB that imitates a Panamax tanker. This ship was installed with a Flettner rotor, a kite and a wind turbine in three different scenarios to see how they can reduce consumption. According to the mathematical values the Flettner rotor was the most effective at utilizing wind power and could save up to 9038 US dollar each day. However, this report has limited itself to look at the ship and its propulsion under conditions with ideal wind direction.
Keywords: Energi; Transport; Maskinteknik; Energy; Transport; Mechanical Engineering